ENSO and Paraná flow variability: Long-term changes in their connectivity - Antico, Andres; Vuille, Mathias (International Journal of Climatology)
The Paraná River of South America is one of the largest rivers in the world. Although the connection between Paraná streamflow and El Niño–Southern Oscillation (ENSO) has been studied before, little is known about the long-term (interdecadal) changes of this connectivity. Here we reveal these changes by analysing long instrumental records of Paraná flow, ENSO indices and other climate variables. We find that flow and ENSO were connected in 1876–1940 and 1983–2016, but disconnected in 1941–1982. Flow variability was more related to central Pacific ENSO fluctuations in 1876–1940 but more linked with eastern Pacific ones in 1983–2016, probably because the ENSO–Paraná basin teleconnection was different in the two periods. ENSO-related Pacific climate anomalies exhibited their smallest amplitudes during the disconnection period 1941–1982, suggesting that the ENSO–flow link vanishes when ENSO is weak. We also find that the ENSO–flow disconnection coincided with the coldest phase of the Interdecadal Pacific Oscillation (IPO) in the study period. Thus, the IPO may be modulating the ENSO–flow connectivity. Interestingly, during the disconnection years (1941–1982), flow was related to climate variability observed in sectors of the southern South Atlantic and tropical North Atlantic oceans. This and the other empirical results presented here provide new insights into the Paraná response to ENSO and thus provide valuable information for future mechanistic studies on this response. Fil: Antico, Andres. Universidad Nacional del Litoral. Instituto de Humanidades y Ciencias Sociales del Litoral. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Santa Fe. Instituto de Humanidades y Ciencias Sociales del Litoral; Argentina Fil: Vuille, Mathias. State University Of New York. University At Albany.; Estados Unidos